The influence of patterned nanofiber meshes on human mesenchymal stem cell osteogenesis - Martins, Albino (2011)
A specially designed electroconductive collector enables the electrospinning of P-NFM composed of areas of parallel/uniaxially aligned fibers and areas of random/orthogonal nanofiber distribution. The biological relevance of P-NFM is demonstrated using hBMSCs as an autologous cell source. The structures induce cell orientation along the uniaxially aligned fibers, mainly during earlier culturing periods under basal and osteogenic differentiation conditions. The microtopography of the P-NFM also controls the deposition of mineralized extracellular matrix along the pre-defined fiber direction. Genotypic characterization confirms the successful differentiation into the osteogenic lineage.